Environmental Narratives and Sustainable Development in Kaṭaici Vivacāyi - Manivannan, Murugesan (INTI International University, 2025)
This paper explores the representation of environmental and global transformations in the Tamil film Kaṭaici Vivacāyi (The Last Farmer), directed by Manikandan and awarded a National Film Award, India. It delves into the Sustainable Development Goals (SDGs), highlighting their interconnected economic, social, and environmental dimensions. As sustainable development has become a pivotal framework for social progress globally, this study analyses how the film integrates these goals into its narrative. Kaṭaici Vivacāyi offers a unique perspective on pressing global issues and environmental degradation, serving as a vital medium for raising awareness and fostering dialogue on these interconnected challenges. The analysis reveals the film’s alignment with contemporary SDGs, vividly portraying various social and environmental issues such as industrial animal farming, hybrid seed usage, urbanisation, and the practices of farmers within an industrialised context. Employing a qualitative descriptive methodology, this research examines the environmental, social and economic elements through the lens of the three pillars of the SDGs.